Ready to Work Program Uses Training and Mentoring Methods for Micro Businesses in Bali Province: Program Ready to Work Menggunakan Metode Pelatihan dan Pendampingan Bagi Usaha Mikro di Provinsi Bali - Br Sitepu, Sri Nathasya; Teguh, Monika; Sienatra, Krismi Budi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Micro business units have difficulty maintaining business units. Micro business units are difficult to grow into small business units to become medium business units. The ready to work program aims to help micro-enterprises in Bali Province. The purpose of the ready-to-work program is to provide entrepreneurial knowledge and maximize the use of social media as a means of promotion and transactions for micro-enterprises. Program participants are 20 residents of Bali Province. The micro business unit that was accompanied focused on the food and beverage business. The ready-to-work program uses training and mentoring methods that are carried out offline and online. The ready to work program lasts for one year by lecturers and students of Ciputra University Surabaya. The results of the ready-to-work program are divided into two groups: 1) increasing entrepreneurial knowledge so that participants can understand and apply the seven basic competencies of entrepreneurs, 2) Micro businesses are able to use social media (Instagram) as a medium of promotion and transactions (sales).